Application Of Computational Fluid Dynamics In An Outer Channel Of Orbal Biological System - Kamal, Nurzulaikha Mohd (Universiti Sains Malaysia, 2019)
Orbal Biological System (OBS) is one of the modified oxidation ditches which claimed as the most energy efficient, safest and has the lowest maintenance. The OBS can be easily modified to meet wide assortment of influent conditions and effluent requirements. There are three channels in OBS, outer channel, middle channel and inner channel. The outer channel of OBS has the largest volume among the three channels, which is about 50% of the total volume of the system. It is crucial to study the operating system of the outer channel of OBS as it contribute to the highest energy consumption in the system. This is because in the wastewater treatment system nowadays, the quality standards of the effluent are not only the criteria to be focused on, but other aspects such as economic also are taken as considerations. Therefore, the study was conducted to understand the function and the effect of the number of aeration discs in the outer channel of the OBS. The Computational Fluid Dynamics (CFD) model is developed to have a better picture of the OBS. The simulation in CFD were used to study the behaviour of the influent in the outer channel of OBS and the velocity distribution for different operating conditions in the outer channel of OBS. The result of the CFD model were used to study the relationship between the velocity and the number of aeration discs being used. Based on the study, by turning off some shaft in the outer channel of OBS was contributing to less energy consumption. From the research, the average deviation for the CFD model is 23%, which need improvement in grid generation. The research provides a better understanding of model flow behaviour of a biological treatment system using the simulation tool. It can contribute to a better design of wastewater treatment process models in the future